The Perception of Auditor Career From University Students Perspective - Ramdani, Muhammad Reza; Arumbarkah, Andi Muara; Lestari, Ismi Ayu (JEMA: Jurnal Ilmiah Bidang Akuntansi dan Manajemen, 2019)
This study explores the perceptions of accounting students about their selection in a career as an auditor through several indicators. This study is to see what indicators are the choice of students in their career as auditors. The approach used was quantitative descriptive. The total sample of 100 students from Muslim University of Indonesia and Muhammadiyah University of Makassar. The method of data collection was through questionnaires distributed to students and by purposive sampling method. The results of the study showed that financial appreciation, professional recognition, and market considerations have a positive and significant effect while professional training, work environment and personality have a positive and not significant effect on auditor career selection and social value variables that have a negative and insignificant effect on career choice as an auditor. Financial award is a dominant variable in the career choice of students as auditors.